2007
DOI: 10.1055/s-2006-927085
|View full text |Cite
|
Sign up to set email alerts
|

Radiologische Evaluation der Variationsbreite der Pfannenpositionierung bei konventioneller Hüftendoprothesenversorgung

Abstract: The common implantation technique yielded significant variation with respect to anteversion and inclination. The application of computer-aided navigation in the placement of acetabular cups would help to improve accuracy and reproducibility considerably in total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
(17 reference statements)
0
8
0
4
Order By: Relevance
“…Many studies have suggested that there is improved cup positioning with navigation-based implantation (Saxler et al 2004a, Honl et al 2006, Kalteis et al 2006a, Leichtle et al 2007, Parratte and Argenson 2007). However, individual studies are too small to allow conclusive statements on the potential benefit of navigation in THA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have suggested that there is improved cup positioning with navigation-based implantation (Saxler et al 2004a, Honl et al 2006, Kalteis et al 2006a, Leichtle et al 2007, Parratte and Argenson 2007). However, individual studies are too small to allow conclusive statements on the potential benefit of navigation in THA.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed later, however, various severe pitfalls and possible inherent error or bias must be considered. As with total knee arthroplasty and screw positioning in spinal surgery, the major benefit of navigation is the reduction of outliers, that is, cup positioning beyond the “safe zone” with an inclination of 40° (± 10°) and anteversion of 15° (± 10°) (Saxler et al 2004a, Honl et al 2006, Kalteis et al 2006a, Minoda et al 2006, Leichtle et al 2007, Parratte and Argenson 2007, Sugano et al 2007). Moreover, it seems that navigation-based cup positioning in THA meets the criteria of evidence by reducing the amount of outliers in cup orientation (Leenders et al 2002, Stipcak et al 2004, Ottersbach and Haaker 2005, Kalteis et al 2006a, Parratte and Argenson 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In einer aktuellen Untersuchung an einem Kollektiv von 950 konventionell implantierten Hüftendoprothesen fanden sich radiologisch bestimmte Werte für die Inklination zwischen 28°und 75°, für die Anteversion zwischen −9°und 50°. Bei einer tolerierten Abweichung von ± 10°fanden sich immerhin 34,5 % der Pfannen außer-halb des "Sicherheitsbereichs" und zwar unabhängig von der Erfahrung des einzelnen Operateurs [6]. Wir stellen in diesem Artikel die von uns entwickelte konventionelle Hüftpfannennavigation mit dem Röntgenbildwandler vor.…”
unclassified